The Influence Of Problem Based Learning (Pbl) Model on Student’ Ability In Scientific Work and Creativity in Natural Science Lesson Given to Fourth Grade Studentst in SDN Gerimak Indah Narmada Lombok Barat. - Parziyah, Parziyah (Journal of Islamic Education, 2020)
Scientific work and creativity are two important things in learning process, particularly Natural Science lesson. PBL model may improve students’ scientific work and creativity. This study aims to find out: 1) the process of PBL model implementation on the students ability in scientific work and creativity in Natural Science lesson given to fourth grade Student in SDN 2 Gerimak Indah Narmada Lombok Barat. 2) the influence of PBL model on the students ability in scientific work and creativity regarding Natural Science lesson given to the fourth grade students in SDN 2 Gerimak Indah Narmada Lombok Barat.     This study employs quantitative research method of quasi experiment of control group design. This study is conducted using PBL model in experimental class and conventional method in controlled class. After carrying out and learning process, scientific work is measured based on the observation/practicum and the creativity is measured using questionnaire. The analysis result of this study can be seen based on the scientific work result as shown by 25 students in experimental class who obtain 76% with a high qualification, and 36% in controlled class with adequate qualification. Based on the big experimental class 92%. The difference is 12% compared to controlled class which reaches 80%. The validity and reability analysis use bivariate pearson correlation, with Ttabel = 0,396, and all items are considered reliable as proved by cronbach’s alpha = 0,743 ≥ 0,70.     The normality test has a normal distribution since it has Asymp Sign ≥ 0,05, the achievement or learning outcomes of experimental class has Sign 0,146 and controlled class has Sign  0,846. Thus, it can be concluded that the data has a normal distribution. The homogeneity test with a significant level of 0,05 in experimental class in categorized as homogenous because of the significant value that is 0,111 since the significant value obtained in homogeneity test is ≥ 0,05. The data  on the dependent variable point out that the variable is always close to the diagonal line, therefore, the data are considered homogeneous. In the hypotheis testing, 25 respondents in experimental class have mean 82,23, meanwhile, the mean of 25 respondents in controlled class is 70,56, and Tcount = 5,035, with a significant level 0,05/5% and the Ttabel is 2,064. Based on the data, it can be concluded that Tcount ≥ Ttabel. So H0 is rejectet and Ha is accepted. In conclusion, based on the data, problem based learning (PBL) model affects the students’ scientific work and creativity in Natural Science lesson given to fourth grade student in Grimak Indah Narmada Lombok Barat in the Academic Year of 2017/2018.